Export, sssembly-line FDI or FDI with the possibility of technology diffusion: Optimal entry mode for multinationals - Tanmoyee Banerjee; Nilanjana Mitra (Fondazione Eni Enrico Mattei (FEEM), 2008)
The paper tries to evaluate the optimal entry mode of a Multinational Company that is choosing among export, fragmented production structure with assembly-line FDI in LDC or complete production in LDC with FDI. The results show that if the plant installation cost is sufficiently high then the firm will find it profitable to export the finished product to the LDC market and the Government will not exercise any IPR restriction. If plant installation cost is below a certain critical level the MNC chooses complete LDC production with FDI over assembly-line FDI if the IPR restriction is strong, where the model assumes that a fake producer can copy the product if complete production takes place in LDC. In such a situation government will choose to protect IPR if government earning exceeds the cost of IPR protection, otherwise no monitoring is the optimal strategy of the government and MNC will choose the strategy of fragmented production structure and assembly-line FDI will take place in LDC.
Keywords: L11; O34; 330; Export; Assembly-line FDI; FDI with Complete Production; IPR Protection